SAT-351 CYP11B1 Is a Highly Accurate Marker of Malignancy in Functioning Adrenocortical Tumors - Pereira, Sofia (J Endocr Soc, 2019)
Autonomous steroid secretion is a common feature of adrenocortical carcinomas (ACCs). However, steroid overproduction in ACC is not always clinically evident owing to inefficient steroidogenesis with increased release of steroid precursors in result of an incomplete pattern of steroidogenic enzyme expression Immunohistochemical expression of protein involved in steroidogenesis, namely steroidogenic acute regulatory protein (StAR), 11β-hydroxylase (CYP11B1), aldosterone synthase (CYP11B2) and 17α-hydroxylase, were analyzed in ACCs (n=15), adenomas presenting with Cushing Syndrome (CUSH) (n=15) and clinically non-functioning adenomas (nACA) (n=15). The percentage of the stained area for each protein was analyzed using the ImageJ software for computerized morphometric quantification. CYP11B2 was found to be poorly expressed in all the tumors analyzed. CYP11B1, StAR and 17α-hydroxylase expression was significantly lower in ACCs when compared to CUSH, while CYP11B1 showed to be the most discriminative steroidogenic enzyme to distinguish ACC from CUSH with a sensitivity of 100% and specificity of 92%. CYP11B1 and CYP11B2 dual negativity presented a specificity of 100% for the differential diagnosis between ACC and CUSH. In conclusion, ACC depicted an incomplete pattern of steroidogenic protein expression, with decreased StAR, CYP11B1 and 17 α-hydroxylase, which could explain the predominant secretion of steroid precursors. Moreover, CYP11B1 is a highly accurate marker to differentiate ACC from CUSH. Thus, CYP1B1 negativity has the potential of being useful as a diagnostic tool to identify malignancy in steroid secreting adrenocortical tumors. Funding: This work was funded by FCT (PTDC/MEC-ONC/31384/2017).